Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b: \(=2^{11}\left(1+2\right)=2^{11}\cdot3⋮3\)
c: \(=2\left(1+2\right)+2^3\left(1+2\right)+...+2^7\left(1+2\right)\)
\(=3\left(2+2^3+...+2^7\right)⋮3\)
\(6+6^2+\cdot\cdot\cdot+6^{10}\)
\(=6\cdot\left(1+6\right)+6^3\cdot\left(1+6\right)+\cdot\cdot\cdot+6^9\cdot\left(1+6\right)\)
\(=6\cdot7+6^3\cdot7+\cdot\cdot\cdot+6^9\cdot7\)
\(=7\cdot\left(6+6^3+\cdot\cdot\cdot+6^9\right)⋮7\)
\(\Rightarrow6+6^2+\cdot\cdot\cdot\cdot+6^{10}⋮7\)
a, 11 + 112 + 113 + ... + 117 + 118
= (11 + 112) + (113 + 114) + ... + (117 + 118)
= 11(1 + 11) + 113(1 + 11) + ... + 117(1 + 11)
= 11.12 + 113.12 + .... + 117.12
= 12(11 + 113 + ... + 117) chia hết cho 12
b, 7 + 72 + 73 + 74
= (7 + 73) + (72 + 74)
= 7(1 + 72) + 72(1 + 72)
= 7.50 + 72.50
= 50(7 + 72) chia hết cho 50
c, 3 + 32 + 33 + 34 + 35 + 36
= (3 + 32 + 33) + (34 + 35 + 36)
= 3(1 + 3 + 32) + 34(1 + 3 + 32)
= 3.13 + 34.13
= 13(3 + 34) chia hết cho 13
Ta có: A= 3+3\(^2\)+3\(^3\)+3\(^4\)+3\(^5\)+3\(^6\)+3\(^7\)+3\(^8\)+3\(^9\)+3\(^{10}\)
\(\Rightarrow\)A= (3+3\(^2\)) +(3\(^3\)+3\(^4\))+(3\(^5\)+3\(^6\)) +(3\(^7\)+3\(^8\))+(3\(^9\)+3\(^{10}\))
\(\Rightarrow\) A= 12 + 3\(^2\)(3\(^1\)+3\(^2\))+3\(^4\)(3\(^1\)+3\(^2\)) +3\(^6\)(3\(^1\)+3\(^2\)) + 3\(^8\)(3\(^1\)+3\(^2\))
\(\Rightarrow\) A= 12 + 3\(^2\). 12+3\(^4\) . 12+3\(^6\) .12+ 3\(^8\) .12
\(\Rightarrow\)A= 12 . ( 3\(^2\)+3\(^4\) +3\(^6\)+ 3\(^8\))
Vì 12 \(⋮\)4 \(\Rightarrow\)12 . ( 3\(^2\)+3\(^4\) +3\(^6\)+ 3\(^8\)) \(⋮\)4 hay A \(⋮\)4
kệ mịa mày